Tissue Tregs and Maintenance of Tissue Homeostasis - Shao, Qing; Gu, Jian; Zhou, Jinren; Wang, Qi; Li, Xiangyu; Deng, Zhenhua; Lu, Ling (Frontiers in Cell and Developmental Biology, 2021)
Regulatory T cells (Tregs) specifically expressing Forkhead box P3 play roles in suppressing the immune response and maintaining immune homeostasis. After maturation in the thymus, Tregs leave the thymus and migrate to lymphoid tissues or nonlymphoid tissues. Growing evidence indicates that Tregs with unique characteristics also have significant effects on non-lymphoid peripheral tissues. Tissue-resident Tregs, also called tissue Tregs, do not recirculate in the blood or lymphatics and attain a unique phenotype that is distinct from common Tregs in circulation. This review first summarises the phenotype, function, and cytokine expression of these Tregs in visceral adipose tissue, colon, muscle, and other tissues. Then, how Tregs are generated, home, and are attracted to and remain resident in the tissue is discussed. Finally, how an increased understanding of these tissue Tregs might guide clinical treatment is discussed.